Cervical cancer and human papilloma virus vaccination: gap and barriers - Garg, Ram Kumar; Sharma, Bhartendra (International Journal Of Community Medicine And Public Health, 2022)
Cervical cancer, which is mostly caused by infection with the human papillomavirus (HPV), is the second most common malignancy in women worldwide and the main illness affecting Indian women. It has been demonstrated that many developing countries lack basic information and health-seeking behaviours, necessitating the need for an effective awareness and immunization programme. For public health, the HPV vaccine is essential. For all females who can afford it, the Indian Academy of Paediatrics Committee on Immunization (IAPCOI) suggests administering the HPV vaccine. Females as young as 9 years old and those who have not received all recommended vaccinations between the ages of 13 and 26 can receive vaccinations. Cervical cancer can be prevented in a number of ways, however vaccination is currently the most effective strategy. The most effective means of preventing cervical cancer include HPV vaccination and routine cervical screening. Before beginning this chemoprophylaxis against cervical cancer, parents and caregivers of the child must receive education regarding HPV vaccine. In order to mobilise the scientific, public health, and civil society communities to adopt the vaccination policy, gaps and challenges to HPV vaccination access and delivery must be addressed.